Incentives and creativity - Bruno S. Frey; Michael Gibbs; Susanne Neckermann; Christiane Bradler; Arne Jonas Warnke; Christoph Siemroth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
In knowledge-intensive economies, ideas and innovation are key drivers of a company's competitiveness and success. In such a climate a company must strategise methods designed to incentivize the generation of new ideas and build a culture that rewards the production of knowledge. Many scholars have suggested that motivating creative performance is fundamentally different from motivating performance in simple and routine tasks. Nevertheless, economic studies investigated the effect of financial incentives on employees' performance mainly by observing employees performing simple and routine tasks while effects on creative performance have received little scientific attention so far. For routine tasks, a myriad of studies confirm that financial incentives have a positive effect on performance because employees increase their effort insofar as their potential benefit from additional output exceeds the cost of that effort. Moreover, a substantial number of studies document that employees' performance is not only triggered by rewards contingent on performance but employees do also reciprocate financial rewards that are allocated independently of individual performance, such as wage premia, with an increase in their performance. However, it remains unclear to which extent previous results can be transferred to creative tasks. The present research covers two empirical studies that investigate whether financial rewards such as performance independent bonuses and performance rewards foster creativity and idea generation among employees and to what extent the effect of incentives differs depending on the type of reward that is offered. – – Ideenreichtum und Innovationen stellen in wissensintensiven Volkswirtschaften den Schlüssel zu Wettbewerbsfähigkeit und Erfolg von Unternehmen dar. In einem solchen Umfeld muss ein Unternehmen strategisch Maßnahmen entwickeln, um Anreize für neue Ideen im Unternehmen zu schaffen und eine Kultur aufbauen, in der Wissensproduktion honoriert wird. Die vom SEEK-Forschungsprogramm finanzierte Forschungsarbeit behandelt zwei empirische Studien, die sich mit der Frage beschäftigen, ob finanzielle Belohnungen wie leistungsunabhängige Zusatzzahlungen oder Leistungsprämien Kreativität und Einfallsreichtum unter den Mitarbeitern fördern, und inwieweit die Effekte der Belohnungen je nach Art der Honorierung variieren.
Keywords: 330